Factors Associated With Involuntary Psychiatric Hospitalization of Youths in China Based on a Nationally Representative Sample - Geng, Feng; Jiang, Feng; Conrad, Rachel; Liu, Tingfang; Liu, Yuanli; Liu, Huanzhong; Tang, Yi-lang (Frontiers in Psychiatry, 2020)
Objective: This nationally representative sample investigates demographic, diagnostic and clinical features associated with both voluntary and involuntary psychiatric hospitalization among children and adolescents psychiatrically hospitalized in China. Method: As part of an official national survey, 41 provincial tertiary psychiatric hospitals in China were selected. Data from 196 children and adolescents who were discharged from these psychiatric hospitals from March 19 to 31, 2019 were retrieved and analyzed. Results: 1. Psychotic symptoms, depressive symptoms and self-injury/suicide were the most common reasons of admission. Girls were significantly likely to be admitted due to depressive symptoms, whereas boys were more likely to be admitted due to aggressive behaviors. 2. The overall rate of involuntary admission was 32.1% (N=63). Compared to patients who were admitted voluntarily, those who were admitted involuntarily had lower GAF scores on admission, were older, were more likely to present with psychotic symptoms, manic symptoms or aggressive behavior as primary reason for admission, were less likely to present with depressive symptoms, had a significantly longer length of stay, were more likely to be diagnosed with schizophrenia and were less likely to be diagnosed as depressive disorder. 3. A logistic regression showed that depressive symptom as primary reason for admission was significantly associated with voluntary admission (OR=0.159, p<0.001), along with two other factors: age (p<0.01) and a lower GAF score at admission (p<0.001) were significantly associated with involuntary admission. Conclusion: The rate of involuntary psychiatric hospitalization among children and adolescents is higher in China than in other regions. Developing more specific and more operational criteria to guide involuntary psychiatric admission for child and adolescent patients is of urgency and great importance to ensure appropriate treatment of these patients and protect their rights.